Poly(methyl methacrylate-co-butyl acrylate-co-acrylic acid): Physico-chemical characterization and targeted dye sensitized solar cell application. (15th October 2016) - Shanti, R.; Bella, F.; Salim, Y.S.; Chee, S.Y.; Ramesh, S.; Ramesh, K.
Abstract: A random poly(methyl methacrylate- co -butyl acrylate- co -acrylic acid) [P(MMA- co -BA- co -AA)] was synthesized via emulsion polymerization utilizing thermally-activated persulfate radicals. The successful synthesis of high molecular weight copolymer at high monomer conversion rate was confirmed by NMR study. Various techniques were employed to characterize the structure, electrical and thermal properties of copolymer. The removal of unreacted monomers from the end product by casting technique was rationalized from the disappearance of CC FTIR characteristic peak in the cast film. The drying of the emulsion above the glass transition temperature ( T g  = 24 °C) yields an amorphous film with smooth surface morphology. The suitability of the formed continuous film as a base polymer for iodide-based electrolytes in dye sensitized solar cell (DSSC) fabrication was investigated. The polymeric solid state electrolytes (PSSE) were formulated by varying the doping concentrations of sodium iodide (NaI) in fixed ratio of iodine (I2 ) and mixtures of ethylene carbonate: propylene carbonate (EC:PC, 1:1). The DSSC fabricated using PSSE with 15 wt.% NaI showed the highest solar-to-electrical energy conversion efficiency ( η ) of 3.22% under 100 mW cm − 2 sunlight intensity. This implies that the physico-chemical properties of the synthesized copolymer are suitable for the development of photoelectrochemical device. Graphical abstract: Highlights: We have synthesised ultra-high molecular weight copolymer based on acrylates. Highest conversion efficiency of 3.22% at 1 Sun, and prolonged durability is attained. It is not always true that copolymer with large molecular weight will obstruct electrochemical function.